2013
DOI: 10.1590/s0103-90162013000300005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic potential of common bean parents for plant architecture improvement

Abstract: In common bean (Phaseolus vulgaris L.) breeding, plant selection that associate erect plant architecture, high yield, and grains with good commercial acceptance has been the choice of breeders. Thus, this study aimed to evaluate potential parents, to obtain promising segregating populations that associate high yield, erect plant architecture and carioca grain type, as well as to obtain information on heterosis, general and specific combining ability of these parents regarding grain yield and traits related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 20 publications
3
26
0
5
Order By: Relevance
“…We observed a predominance of estimates of additive variance related to dominance for the 3 populations in the 2 seasons (Table 4). Baldissera et al (2012) and Silva et al (2013b) also observed a predominance of additive effects in HD genetic control. Heritability estimates of family means ranged from 55 to 76% for the 3 populations over the 2 seasons (Table 4).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…We observed a predominance of estimates of additive variance related to dominance for the 3 populations in the 2 seasons (Table 4). Baldissera et al (2012) and Silva et al (2013b) also observed a predominance of additive effects in HD genetic control. Heritability estimates of family means ranged from 55 to 76% for the 3 populations over the 2 seasons (Table 4).…”
Section: Resultsmentioning
confidence: 88%
“…Two hypotheses explain these results: i) reduced sample size of F 2:3 progenies and ii) high environmental influence in the expression of HD and PAG. High estimates of phenotypic correlation between HD and PAG using common bean lines were also observed by Silva et al (2013b) and Moura et al (2013). To discriminate the 32 F 2:3 families from each population with 80% accuracy (R 2 = 0.80), it was necessary to evaluate the HD of at least 39 plants in each plot (Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, when there is interest in using a specific parent to create hybrids, SCA estimates are useful to select the best parental combination (Silva et al, 2013). If, for example, there is a particular interest in Q4205, a cross with Bagual is recommended, since the resulting hybrids showed the highest SCA.…”
Section: Resultsmentioning
confidence: 99%
“…Neste contexto, os cruzamentos dialélicos se destacam na seleção de genitores e, em particular, os dialelos parciais, quando o objetivo é reunir fenótipos favoráveis que se encontram em grupos distintos de genitores, pois, nesse caso, não são de interesse as combinações dentro de cada grupo. Os dialelos parciais têm sido utilizados em diversas culturas, como trigo (Pimentel et al, 2013), tomate (Pádua et al, 2010) e feijão (Silva et al, 2013).…”
Section: Introductionunclassified